(untitled) (Dimensión Antropológica, 2019)
Interviews with relatives make it possible to obtain useful data for finding lost or missing persons and identifying dead people, two essential problems in forensic anthropology. In this paper, the utility, scope and limitations of this tool are highlighted, emphasizing the need to standardize the procedures for the collection of ante-mortem data (AM) useful for confronting with post-mortem data (PM) in the identification process. It also points out the need to include questions in the interview regarding the circumstances surrounding the event, to constitute proof in cases of forced disappearance. This work is the product of the authors’ professional practice, as well as the analysis of various search and identification protocols employed by Latin American forensic anthropology teams. Finally, the article addresses the need to professionalize and raise awareness among those who conduct interviews with family members, in which the Forensic Anthropologist is the ideal specialist for this task, and the importance for forensic anthropology to incorporate international protocols on this matter.